Influence of zinc, lead, cadmium pollutants on the microflora of hawthorn leaves [Sporobolomyces roseus, Aureobasidium pullulans] - Bewley, R.J.F; Campbell, R (Microbial ecology, 1980)
Transect studies were conducted to determine the relative effects of zinc, lead, and cadmium pollution on microorganisms occurring on hawthorn leaves at varying distances from a smelting complex.Sporobolomyces roseus was absent from the most heavily contaminated leaves but, although lead was inhibitory, other environmental factors were also important in determining its overall population level. Conversely,Aureobasidium pullulans and nonpigmented yeasts showed a significant partial positive correlation with lead but were inhibited by zinc and/or cadmium. Numbers of bacterial colonies were only slightly reduced by the combined effect of all three metals, but total numbers of bacteria were highly negatively correlated with lead. Filamentous fungi, isolated by leaf washing, were only slightly inhibited by all three metals, and the degree of mycelial proliferation on senescent leaves was little affected by heavy metal pollution. Computer-generated maps were produced of the distribution ofA. pullulans in relation to zinc and lead fallout.